All that glitters is not gold: the need to consider desirable and undesirable immune aspects of oncolytic virus therapy. (2nd January 2016) - Clements, Derek R; Kim, Youra; Gujar, Shashi A; Lee, Patrick WK
Abstract : Oncolytic viruses (OVs), a novel class of anticancer therapeutic agents, can overturn cancer-mediated immunosuppression and initiate antitumor immunity. Contrary to this paradigm, our recent study illustrates that oncolytic reovirus transiently augments cancer-associated immunosuppression immediately following its therapeutic administration. To achieve the optimum efficacy for OV-based anticancer therapies, the pathophysiological as well as clinical implications of this phenomenon need to be considered.